The right to science in sexual and reproductive health and the legal status of the human embryo - Silke Dyer; Alison B. Edelman; Asha S. George; Tari Turner; Joanna N. Erdman (Sexual and Reproductive Health Matters, 2025)
Through the examination of scientific evidence related to human embryo development, the aim of this commentary is to support the right to science in sexual and reproductive health, to outline why science supports a legal approach to embryos as the biological material of human life but not as human persons, and to recognise that international human rights law adopts this approach in the protection of sexual and reproductive health and rights.